2018
DOI: 10.1016/j.yjmcc.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Etiology-dependent impairment of relaxation kinetics in right ventricular end-stage failing human myocardium

Abstract: Force development at resting heart rate is not impacted by cardiac pathology, but kinetics are impaired and the magnitude of the impairment depends on the underlying etiology. Focusing on restoration of myocardial kinetics will likely have greater therapeutic potential than targeting force of contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 32 publications
6
36
0
Order By: Relevance
“…; Chung et al. ), nonfailing trabeculae typically display a positive FFR, as developed force increases at increased stimulation frequencies. Failing trabeculae typically have a negative FFR as developed force decreases at increased stimulation frequencies.…”
Section: Discussionmentioning
confidence: 98%
“…; Chung et al. ), nonfailing trabeculae typically display a positive FFR, as developed force increases at increased stimulation frequencies. Failing trabeculae typically have a negative FFR as developed force decreases at increased stimulation frequencies.…”
Section: Discussionmentioning
confidence: 98%
“…However, on average these previous studies found no or little difference in developed contractile strength of viable myocardium at rest. A recent study conducted over 6 years (10) on >80 human hearts confirmed that there was indeed no significant difference inactive developed force of viable right ventricular trabeculae between failing and non-failing myocardium at rest. This may seem at odds with our view of heart failure as predominantly a weak heart, but this outcome is actually expected given the fact that the failing heart at rest, and the non-failing heart at rest, produce a very similar cardiac output.…”
Section: Introductionmentioning
confidence: 94%
“…When human myocardium in vitro is subject to the conditions of exercise, causing an elevation in heart rate, contractile deficits clearly become obvious in the end-stage failing myocardium. Healthy human myocardium increases developed force when heart rate is elevated, failing myocardium either increases less, but more often does not increase at all or even decreases when heart rate is elevated (10, 16, 40). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations